2022
DOI: 10.1055/a-1834-7101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of guidewire caliber on ERCP outcomes: Systematic review and meta-analysis comparing 0.025- and 0.035-inch guidewires

Abstract: Introduction The impact of guidewire caliber on ERCP outcomes are not clear. Recent studies have compared two guidewires, 0.035” and 0.025” in randomized controlled trials (RCTs). We performed a systematic review and meta-analysis of available RCTs to assess if different caliber would change the outcomes in ERCP. Methods A systematic search of PubMed/Medline, Embase, Cochrane, SciELO, Global Index Medicus and Web of Science was undertaken through November 23rd, 2021 to identify relevant RCTs comparing the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In the present study, the curvedtip guidewire showed a higher biliary cannulation rate than the straight-tip guidewire, and this result showed a similar trend regardless of the guidewire type (NGW or CGW). One study using the curved-tip type showed a tendency toward a higher cannulation rate with the 0.025-inch guidewire (0.035-inch vs. 0.025-inch: 86% vs. 96%, respectively), while other studies using the straight-tip type reported higher cannulation rates with the 0.035-inch guidewire (0.035-inch vs. 0.025-inch: 82% vs. 80.6%, respectively) [6,8]. The ampulla has a papillary fold between the common bile and pancreatic ducts [24].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the present study, the curvedtip guidewire showed a higher biliary cannulation rate than the straight-tip guidewire, and this result showed a similar trend regardless of the guidewire type (NGW or CGW). One study using the curved-tip type showed a tendency toward a higher cannulation rate with the 0.025-inch guidewire (0.035-inch vs. 0.025-inch: 86% vs. 96%, respectively), while other studies using the straight-tip type reported higher cannulation rates with the 0.035-inch guidewire (0.035-inch vs. 0.025-inch: 82% vs. 80.6%, respectively) [6,8]. The ampulla has a papillary fold between the common bile and pancreatic ducts [24].…”
Section: Discussionmentioning
confidence: 95%
“…Although a 0.035-inch guidewire was more frequently used because of its stiffness, recently, a highperformance 0.025-inch hydrophilic-coated guidewire has been developed and widely used [5,6]. In a recent meta-analysis of biliary cannulation according to the guidewire caliber [8], the primary biliary cannulation rates for the 0.035-and 0.025-inch guidewires were 82.0% and 80.6% (relative ratio, 1.02) and the PEP rates were 6.6% and 6.2% (relative ratio, 1.15), respectively. One study that was not included in the meta-analysis showed a similar biliary cannulation rate; however, the 0.025-inch guidewire had a lower frequency of ampulla contact and shorter cannulation time compared to those with the 0.035-inch guidewire [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation